PENYULUHAN EFEKTIF MENINGKATKAN PENGETAHUAN PEMBERANTASAN JENTIK NYAMUK AEDES AEGYPTI PADA ANAK SEKOLAH DASAR DI KOTA GIANYAR - Damayanti, Putu Ayu Asri; Laksemi, Dewa Ayu Agus Sri; Diarthini, Ni Luh Putu Eka (Coping: Community of Publishing in Nursing; Vol 12 No 1 (2024): Februari 2024DO - 10.24843/coping.2024.v12.i01.p03, 2024)
Aedes aegypti is a vector for Dengue disease which is still endemic in Bali, including Gianyar Regency. Eradicating mosquito larvae is an effective vector control method. Communities starting from elementary school age children are expected to eradicate mosquito larvae independently. Elementary school children must have sufficient knowledge to be able to eradicate larvae. One effective method of increasing knowledge is through counseling. This research aims to determine the effectiveness of counseling for children at SD 1 Gianyar City to increase knowledge. A cross-sectional analytical research design was carried out involving 92 fifth grade elementary school students. Knowledge was measured by questionnaires carried out before and after counseling. The research results showed that the median knowledge score before and after counseling was 50 and 80. There was a significant difference in knowledge before and after counseling (p=<0,01) with an increase in knowledge of 37.5%. It can be concluded that counseling is effective in increasing the knowledge of SD 1 children in Gianyar City. Health education regarding eradicating larvae from an early age is carried out routinely and simultaneously to support the Dengue disease vector control program.